2022
DOI: 10.3390/cancers14235830
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparity for Patients with Cutaneous Squamous Cell Carcinoma of the Head and Neck: A Systematic Review

Abstract: The incidence of head and neck cutaneous squamous cell carcinoma (HNcSCC) is unevenly distributed between men and women. At present, the mechanism behind this disparity remains elusive. This study conducted a systematic review and meta-analysis of proportions to investigate the disparity between sexes for patients with HNcSCC. PubMed, Scopus, EMBASE, MEDLINE, Emcare and CINAHL were searched in November 2021 and June 2022 (N > 50, English, human), and studies which examined the association between sex and HN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…[19][20][21] Cases of cSCC in the general population indicate that it is more prevalent in males than females. 22 However, this is likely because men spend more time exposed to the sun without adequate protection. 23,24 Similarly, our investigation found that reports of cSCC as an adverse event to medications were overall most prevalent amongst males; however, in certain medication classes, such as monoclonal antibodies, cSCC was more prevalent in females.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Cases of cSCC in the general population indicate that it is more prevalent in males than females. 22 However, this is likely because men spend more time exposed to the sun without adequate protection. 23,24 Similarly, our investigation found that reports of cSCC as an adverse event to medications were overall most prevalent amongst males; however, in certain medication classes, such as monoclonal antibodies, cSCC was more prevalent in females.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of cSCC in the general population indicate that it is more prevalent in males than females [ 22 ]. However, this is likely because men spend more time exposed to the sun without adequate protection [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Further, none are derived from a female; while males are more predominately affected by metastatic cSCC, there is increasing suggestion of a sex-related influence on disease progression requiring greater preclinical representation. 48,49 These limitations are compounded by the time to establish these cell lines by clonal outgrowth, followed by a minimum of four but usually beyond 10 passages. 13,14 This is notwithstanding the laborious efforts to comprehensively validate the cell lines to facilitate meaningful correlations between tumour properties and therapeutic sensitivity for responder stratification.…”
Section: Improving Model S Of Me Ta S Tati C C Sccmentioning
confidence: 99%
“…Given distinct differences in the molecular alterations and TME characteristics of tumours of immunocompromised compared to immunocompetent patients, comprehensive screening of both cohorts is critical 46,47 . Further, none are derived from a female; while males are more predominately affected by metastatic cSCC, there is increasing suggestion of a sex‐related influence on disease progression requiring greater preclinical representation 48,49 . These limitations are compounded by the time to establish these cell lines by clonal outgrowth, followed by a minimum of four but usually beyond 10 passages 13,14 .…”
Section: Improving Models Of Metastatic Csccmentioning
confidence: 99%